Does downward nominal wage rigidity dampen wage increases? - Heiko Stüber; Thomas Beissinger (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
Focusing on the compression of wage cuts, many empirical studies find a high degree of downward nominal wage rigidity (DNWR). However, the resulting macroeconomic effects seem to be surprisingly weak. This contradiction can be explained within an intertemporal framework in which DNWR not only prevents nominal wage cuts but also induces firms to compress wage increases. We analyze whether a compression of wage increases occurs when DNWR is binding by applying Unconditional Quantile Regression and Seemingly Unrelated Regression to a data set comprising more than 169 million wage changes. We find evidence for a compression of wage increases and only very small effects of DNWR on average real wage growth. The results indicate that DNWR does not provide a strong argument against low inflation targets.
urn:nbn:de:bsz:100-opus-5144
Keywords: E24; E31; J31; 330; Downward Nominal Wage Rigidity; Wage Stickiness; Wage Compression; Unconditional Quantile Regression; Lohnpolitik; Reallohn; Lohntheorie; Regression; Qualitatives Verfahren; Geldpolitisches Ziel